2015
DOI: 10.1016/j.engfailanal.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of damage caused by siloxanes in stationary reciprocating internal combustion engines operating with landfill gas

Abstract: Failures in reciprocating internal combustion engines operating with landfill gas are not uncommon. In general, damage is located in the combustion chamber surfaces and in the ring grooves, where a layer of non-volatile combustion products is deposited. These deposits attached to the surfaces reduce heat transfer and increase inner temperature, which produces a knocking phenomena damaging the crank bearings and fusing of the piston head material. Lubrication problems also appear due to the formation of a layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Biogas is generally a mixture of 50-70 v% methane, 30-50 v% carbon dioxide, and <6 v% residual compounds such as water vapor, hydrogen sulfide, and siloxanes (Poloncarzova et al, 2011). Hydrogen sulfide and siloxanes must be removed from the biogas to increase the calorific value and avoid damage to the combustion system (Álvarez-Flórez andEgusquiza, 2015, Kapoor et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biogas is generally a mixture of 50-70 v% methane, 30-50 v% carbon dioxide, and <6 v% residual compounds such as water vapor, hydrogen sulfide, and siloxanes (Poloncarzova et al, 2011). Hydrogen sulfide and siloxanes must be removed from the biogas to increase the calorific value and avoid damage to the combustion system (Álvarez-Flórez andEgusquiza, 2015, Kapoor et al, 2020).…”
mentioning
confidence: 99%
“…Removal of hydrogen sulfide can be achieved by biological treatments that are inexpensive and environmentally friendly (more extensive review on removal of hydrogen sulfide by biological treatment can be found in Khoshnevisan et al, 2017). On the other hand, the siloxanes are undesirable in a gas combustion system due to the formation of silicon dioxide (Álvarez-Flórez and Egusquiza, 2015). The silicon dioxide solid deposits damage parts of the combustion system such as pistons, cylinder heads, and valves (Matsui and Imamura, 2010) causing low efficiency and high repair costs (Ajhar et al, 2010).…”
mentioning
confidence: 99%
“…In addition to hydrogen sulphide in biogas, there are several hundred other compounds in trace amounts, among them organohalogen and organosilicon. They can cause the destruction of installations and devices for the energy use of biogas, raising the operating and investment costs for treatment by various methods [3][4][5][6][7][8][9][10][11][12][13][14][15][16] . Commonly occurring in sewage sludge organosilicon compounds -siloxanes play a special role.…”
mentioning
confidence: 99%
“…Analysis of coatings collected from Otto engine cylinder heads was the subject of studies carried out by [27] who concluded that the theoretical O/Si mass rate in the silicate unit (SiO 4 ) 4 -is 2.278; analysing the O/Si ratios indicated 1.67-2.46. It can be concluded that the silica layer on the cylinder head surface is one of the orthosilicate form.…”
Section: Discussion -The Effect Of Minerals Found In the Digestion Rementioning
confidence: 99%
“…piston walls, cylinder heads, spark plugs and valves. In the gas engine combustion process, organic silicon compounds form a solid insoluble coat on the inner piston surface that cause engine damage [27].…”
Section: Discussion -The Effect Of Minerals Found In the Digestion Rementioning
confidence: 99%